(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Work stress has become more prevalent, as has its impact on employees' psychological and physical health. Occupational stress is the second most prevalent workrelated complaint after low back pain. The study aimed to assess the workplace stress and associated variables among health care professionals in the Jazan region, Saudi Arabia. Methods: A correlation cross sectional study; was carried out at Sabya General Hospital in Jazan, Saudi Arabia; during the period from second week of January 2022 to May 2022. The population sample for this study included healthcare employees. Sample calculation was done by Stephen Thompson formula. Results: Nearly one third (32.5%) of participants their age is from 31- to 35 years old, while more than one fourth (27.2%) of participants their age is from 36- to 40 years, and more than one-fifth (20.9%) of participants their age is from 25- to 30 years old. Also, 56.3% of participants are females, while the rest (43.6%) are males. In addition, 49.0% of participants are nurses, 23.1% are general physicians and 13.8% are administrators. More than half (66.3%) of participants have a high stress level. However, there is insignificant association between stress level and job position of healthcare providers (P - value = 0.099). Conclusion: More than half of the participants in this study are exposed to high-stress levels. A higher percentage of nurses have a higher level of stress. Years of experience, working department, and occupational position are the significant correlated the factors which affect the level of job stress.